Chiose al Paradiso di Dante - Pirandello, Luigi 1867-1936; Dante Alighieri 1265-1321 (Le opere, i giorni: i protagonisti della cultura, 1996)
Critical ed. of Pirandello's annotations to an 1837 ed. of Dante's Paradiso conserved at the Vatican and discovered by G. Bolognese, prof. at Flinders Univ., Adelaide (AUS).